2010
DOI: 10.3109/13813451003631421
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum levels of retinol-binding protein 4 with male sex but not with insulin resistance in obese patients

Abstract: Our data show higher RBP4 levels in obese men than in obese women. However, there was no association of RBP4 levels with insulin resistance or other components of the metabolic syndrome. We conclude that obesity might already be associated with elevated RBP4 levels which then show no additional correlation with metabolic markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 26 publications
3
39
0
2
Order By: Relevance
“…Higher circulating levels of leptin and adiponectin are found in women (82,83). On the contrary, higher levels of circulating RBP4 are described in men (35,37,65,67,72). This dimorphism was, however, not shown in all studies (32,73,84,85).…”
Section: Sex-specific Dimorphism Of Rbp4mentioning
confidence: 60%
See 1 more Smart Citation
“…Higher circulating levels of leptin and adiponectin are found in women (82,83). On the contrary, higher levels of circulating RBP4 are described in men (35,37,65,67,72). This dimorphism was, however, not shown in all studies (32,73,84,85).…”
Section: Sex-specific Dimorphism Of Rbp4mentioning
confidence: 60%
“…In several studies, circulating RBP4 levels also did not correlate with insulin resistance, impaired glucose tolerance, T2D, or altered insulin secretion (10,72,(74)(75)(76)(77). In adipose tissue and muscle, insulin-sensitizing agent pioglitazone unexpectedly increased RBP4 gene expression (10).…”
Section: Rbp4 In Childhood/adolescent Obesity and Insulin Resistancementioning
confidence: 99%
“…In addition to lower insulin sensitivity, a negative effect on secretion of β-cells caused by RBP4 is suggested. On the other hand, there is a variety of recent studies that did not find in RBP4 an accurate biomarker of IR and MS in diabetic or normal subjects (26)(27)(28).…”
Section: Introductionmentioning
confidence: 97%
“…However, the associations between RBP4 levels and measures of insulin resistance were not consistent. In several studies, lack of association between RBP4 levels and insulin sensitivity was also observed (21)(22)(23). Inconsistency in the methodology of measuring RBP4 might be a major cause.…”
Section: Discussionmentioning
confidence: 88%